Medial Occipital Lobe Hyperperfusion Identified by Arterial Spin-Labeling: A Poor Prognostic Sign in Patients with Hypoxic-Ischemic Encephalopathy - de Havenon, A.; Sultan-Qurraie, A.; Tirschwell, D.; Cohen, W.; Majersik, J.; Andre, J.B. (American Journal of Neuroradiology, 2015)
SUMMARY: Hypoxic-ischemic encephalopathy carries an uncertain prognosis. We sought to retrospectively assess the prognostic value of arterial spin-labeling MR imaging in 22 adult patients diagnosed with hypoxic-ischemic encephalopathy. Quantitative CBF maps were generated from the M0 map, and arterial spin-labeling data on a per-voxel basis were regionally interrogated via visual inspection and ROI placement. Hyperperfusion was defined as regional increases in CBF of >20% (relative to global CBF) and/or >100 mL/100 g/min. Eleven of 22 patients had prominent bilateral medial occipital lobe hyperperfusion, all of whom died before hospital discharge. One patient who had nondistinct arterial spin-labeling hyperperfusion and restricted diffusion survived. Medial occipital lobe hyperperfusion is a distinctive pattern that merits prospective investigation in a cohort of patients with moderate hypoxic-ischemic encephalopathy to determine its predictive ability in patients with a higher likelihood of survival.ASLarterial spin-labelingHIEhypoxic-ischemic encephalopathyMOLHmedial occipital lobe hyperperfusion